The 2015 migrant crisis and EU Member States: the relation between state fragility and solidarity. Issue 4 (December 2018) - Pusterla, Francesca; Pusterla, Elia
Abstract This paper questions how the EU Member States handled the 2015 migrant crisis. The EU Humanitarian Aid Policy allows the coexistence of unilateralism, partial delegation and full delegation. Consequently, each EU Member State can also act autonomously. The paper records first the presence of different behaviours among EU Member States in the field of humanitarian aid. Second, it finds a correlation between states' concern for the defence of their sovereignty, facing the risk of 'fragilisation', and the propensity to solidarity. Third, this correlation betweenfragility andsolidarity has a causal direction that corroborates the research hypothesis according to which the higher the state fragility, the less its solidarity. Fourth, the article categorises the EU Member States into four groups according to their generosity.